2022
DOI: 10.1088/1755-1315/1063/1/012038
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the entrepreneurial behaviour of farmers to encourage the development of horticultural agribusiness clusters: The case of shallot farmers in Solok Regency, West Sumatera

Abstract: In Indonesia, shallot production fluctuations can impact price fluctuations and even lead to inflation. The government program to develop new production centres of shallot to fill the supply gap during the off-season are expected to stabilize the prices. One of the emerging development centres of shallots is Solok Regency, West Sumatra. A study on farmers’ entrepreneurial behaviour is needed to support the implementation of the development program and analyze the influence of entrepreneurial behaviour on the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Kahan (2012) noted that the behaviors of entrepreneurial farmers can be interpreted as having the skills to capture value in the value chain, improving and managing efficiency in production, promoting new technologies and innovations, maintaining land management, improving management skills, having trust and respect in the business, promoting group entrepreneurship, and managing farm businesses according to longterm plans. In another study, Puspitasari et al (2022) examined the entrepreneurial behavior of horticultural farmers and found similar traits of them being diligent, responding to opportunities, innovative, risk-taking, and independent. In their research on strawberry farming, Besides, farmers' entrepreneurial behavior was shown by the characteristics of risk-taking, responding to opportunities, innovation, and independence (Wijayanti et al 2022).…”
Section: Entrepreneurialmentioning
confidence: 99%
See 2 more Smart Citations
“…Kahan (2012) noted that the behaviors of entrepreneurial farmers can be interpreted as having the skills to capture value in the value chain, improving and managing efficiency in production, promoting new technologies and innovations, maintaining land management, improving management skills, having trust and respect in the business, promoting group entrepreneurship, and managing farm businesses according to longterm plans. In another study, Puspitasari et al (2022) examined the entrepreneurial behavior of horticultural farmers and found similar traits of them being diligent, responding to opportunities, innovative, risk-taking, and independent. In their research on strawberry farming, Besides, farmers' entrepreneurial behavior was shown by the characteristics of risk-taking, responding to opportunities, innovation, and independence (Wijayanti et al 2022).…”
Section: Entrepreneurialmentioning
confidence: 99%
“…Previous empirical studies emphasize the contribution of entrepreneurial behavior and innovative behavior in an agricultural business (Amir, 2015;Wanyonyi & Bwisa, 2015;Faria & Mixon, 2016;Khoshmaram et al 2020;Li et al 2022;Puspitasari et al 2022;and Wijayanti et al 2022). However, the causality and threshold regression of entrepreneurship and innovative behaviors for millennial farmers are largely ignored.…”
Section: The Econometric Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Consumer demand for shallot commodities continues to increase from time to time (Puspitasari et al, 2019). Consumption of shallots in Indonesia was 2.83 kg per capita per year or 0.23 kg per capita per month so national consumption was estimated to reach 731,100 tons per year (Kiloes, et al, 2022;Direktorat Jenderal Hortikultura, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The sale of shallots is carried out by farmers who waiting for buyers came from the drying area or the farmer's house.The collecting traders are marketing agencies that buy shallots directly from farmers. The selling process happens when farmers come directly to the intermediary traders or respondent farmers who come to them(Puspitasari et al, 2022). In general, the collecting traders come from the local village or neighboring villages.…”
mentioning
confidence: 99%